Safety and Tolerability of Anti–microRNA-328 Ophthalmic Solution, SHJ002, in Pediatric Subjects: First-in-Human Clinical Study - Chen, Jiunn-Liang; Lai, Wei-Yu; Lin, Reuy-Tay; Juo, Suh-Hang H.; Liang, Chung-Ling (Clinical therapeutics, 2024)
•Excessive microRNA-328 in the eye is a risk factor for myopia.•An oligonucleotide was designed to neutralize microRNA-328 via eye drops instillation.•No adverse events were found in this trial.•The first-in-human trial demonstrated the novel eye drops was safe and tolerable in children. microRNA-328 has been reported as a risk factor for myopia development. SHJ002 is an antisense for microRNA-328, and SHJ002 was formulated as ophthalmic solution for a novel microRNA therapy. We aimed to investigate the safety and tolerability of SHJ002 ophthalmic solution in children. This was a single-center, open-label, first-in-human trial in healthy children (NCT04928144). All subjects received the study medication. The trial had 2 stages. Stage 1 was an intrasubject dose-escalation study, and stage 2 was the highest tolerable dose study. The SHJ002 ophthalmic solution was instilled in a randomly selected study eye in each participant, whereas the other untreated eye served as a negative control. Three participants were assigned to stage 1, and they received eye drops of 3 concentrations (0.025%, 0.08%, and 0.25%), each of which was used for 3 consecutive days. The highest tolerable dose from stage 1 was used in stage 2 where another 9 participants were recruited for 28-day treatment. Ocular assessments, physical examination, and vital signs were measured to evaluate safety and tolerability. There were 4 boys and 8 girls with a mean age of 12.3 years and a SD of 1.56. All participants were Asians. All 3 concentrations used in stage 1 were well tolerated, and the dose of 0.25% was used in stage 2. There were no reports of discomfort. There was only 1 mild adverse event (punctate keratitis) in the untreated eye in 1 participant, which was deemed as “unrelated to study drug.” SHJ002 is a novel microRNA therapy that uses eye drop instillation. SHJ002 ophthalmic solution is generally safe and tolerable, which warrants further investigations in Phase II and III trials. ClinicalTrials.gov identifier: NCT04928144.